Semaphorin-3a, neuropilin-1 and plexin-A1 in prosthetic-particle induced bone loss. (15th January 2016) - Saad, S.; Dharmapatni, A.A.S.S.K.; Crotti, T.N.; Cantley, M.D.; Algate, K.; Findlay, D.M.; Atkins, G.J.; Haynes, D.R.
Graphical abstract: Abstract: Peri-prosthetic osteolysis (PPO) occurs in response to prosthetic wear particles causing an inflammatory reaction in the surrounding tissue that leads to subsequent bone loss. Semaphorin-3a (SEM3A), neuropilin-1 (NRP1) and plexin-A1 (PLEXA1) are axonal guidance molecules that have been recently implicated in regulating bone metabolism. This study investigated SEM3A, NRP1 and PLEXA1 protein and mRNA expression in human PPO tissue and polyethylene (PE) particle-stimulated human peripheral blood mononuclear cell (PBMC)-derived osteoclasts in vitro . In addition, the effects of tumour necrosis factor alpha (TNFα) on cultured osteoclasts was assessed. In PPO tissues, a granular staining pattern of SEM3A and NRP1 was observed within large multi-nucleated cells that contained prosthetic wear particles. Immunofluorescent staining confirmed the expression of SEM3A, NRP1 and PLEXA1 in large multi-nucleated human osteoclasts in vitro . Furthermore, SEM3A, NRP1 and PLEXA1 mRNA levels progressively increased throughout osteoclast differentiation induced by receptor activator of nuclear factor κB ligand (RANKL), and the presence of PE particles further increased mRNA expression of all three molecules. Soluble SEM3A was detected in human osteoclast culture supernatant at days 7 and 17 of culture, as assessed by ELISA. TNFα treatment for 72 h markedly decreased the mRNA expression of SEM3A, NRP1 and PLEXA1 by human osteoclasts in vitro . Our findings suggest that SEM3A, NRP1 and PLEXA1 may have important roles in PPO, and their interactions, alone or as a complex, may have a role in pathological bone loss progression. Statement of Significance: Peri-prosthetic osteolysis occurs in response to prosthetic wear particles causing an inflammatory reaction in the surrounding tissue that leads to subsequent bone loss. The rate of hip and knee arthroplasty is increasing by at least 5% per year. However, these joint replacements have a finite lifespan, with data from the National Joint Replacement Registry (Australia) showing that the major cause of failure of total hip replacements is aseptic loosening. In aseptic loosening, wear particles liberated from prostheses are phagocytosed by macrophages, leading to release of inflammatory cytokines and up-regulation of osteoclast formation and activity. Semaphorin-3a, neuropilin-1 and plexin-A1 are axonal guidance molecules that have been recently implicated in regulating bone metabolism. This is the first report to show that these molecules may be involved in the implant failure.